Systematic Review of Multilingual Digital Storytelling in Virtual Learning Environments - Ginikachi Prisca Ifenatuora; Olanrewaju Awoyemi; Fadeke Adeola Atobatele (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This systematic review investigates the integration of multilingual digital storytelling within virtual learning environments (VLEs), focusing on its pedagogical value, technological implementation, and implications for inclusive education. Drawing from a comprehensive analysis of peer-reviewed literature published between 2013 and 2024, the review synthesizes findings from empirical studies, theoretical frameworks, and design-based interventions. Key themes identified include the affirmation of learner identity, enhancement of digital and linguistic fluency, and the role of culturally responsive pedagogies in promoting engagement among linguistically diverse learners. The analysis reveals that multilingual digital storytelling supports holistic learning by merging narrative practices with multimodal digital tools, fostering both cognitive and socio-emotional development. However, the review also highlights significant challenges, such as inconsistent assessment methods, limited teacher training, and a lack of longitudinal research. Pedagogical and technological strategies were found to vary based on context, with successful implementations characterized by learner autonomy, accessible tools, and strong instructional design. The paper concludes by proposing targeted recommendations for educators, instructional designers, and policy-makers, and outlines future research directions to advance equity-oriented, multilingual practices in online education. This review contributes to the growing discourse on digital inclusion by positioning multilingual storytelling as a transformative approach in contemporary e-learning landscapes.